TIEMPO DE RETORNO PARA UNA TORMENTA EXTREMA EN LA ZONA CENTRO DE LA PROVINCIA DE MISIONES - SCHONINGER, FÁTIMA; FERNANDEZ, JOSÉ JAVIER; MINELLA, JEAN PAOLO GOMES; BILIGON, LIDIANE; RODRIGUEZ, DARIO TOMAS; MORALES, IVAN LUIS; SEUFERT, ARIANA GISELLE; NILSSON, GUSTAVO GABRIEL PRYTZ (Salão do Conhecimento, 2025)
TIEMPO DE RETORNO PARA UNA TORMENTA EXTREMA EN LA ZONA CENTRO DE LA PROVINCIA DE MISIONES